Evaluation of a novel nutrition education intervention for medical students from across England. Issue 1 (10th February 2012) - Ray, Sumantra; Udumyan, Ruzan; Rajput-Ray, Minha; Thompson, Ben; Lodge, Keri-Michele; Douglas, Pauline; Sharma, Poonam; Broughton, Rachel; Smart, Sandra; Wilson, Rick; Gillam, Stephen; van der Es, Mike J; et al.
Abstract : Objectives: Problems such as hospital malnutrition (∼40% prevalence in the UK) may be managed better by improving the nutrition education of 'tomorrow's doctors'. The Need for Nutrition Education Programme aimed to measure the effectiveness and acceptability of an educational intervention on nutrition for medical students in the clinical phase of their training. Design: An educational needs analysis was followed by a consultative process to gain consensus on a suitable educational intervention. This was followed by two identical 2-day educational interventions with before and after analyses of Knowledge, Attitudes and Practices (KAP). The 2-day training incorporated six key learning outcomes. Setting: Two constituent colleges of Cambridge University used to deliver the above educational interventions. Participants: An intervention group of 100 clinical medical students from 15 medical schools across England were recruited to attend one of two identical intensive weekend workshops. Primary and secondary outcome measures: The primary outcome measure consisted of change in KAP scores following intervention using a clinical nutrition questionnaire. Secondary outcome measures included change in KAP scores 3 months after the intervention as well as a student-led semiqualitative evaluation of the educational intervention. Results: Statistically significant changes in KAP scores were seen immediately after the intervention, and this was sustained for 3 months. Mean differences and 95% CIs after intervention were Knowledge 0.86 (0.43 to 1.28); Attitude 1.68 (1.47 to 1.89); Practice 1.76 (1.11 to 2.40); KAP 4.28 (3.49 to 5.06). Ninety-seven per cent of the participants rated the overall intervention and its delivery as 'very good to excellent', reporting that they would recommend this educational intervention to colleagues. Conclusion: Need for Nutrition Education Programme has highlighted the need for curricular innovation in the area of clinical health nutrition in medical schools. This project also demonstrates the effectiveness and acceptability of such a curriculum intervention for 'tomorrow's doctors'. Doctors, dietitians and nutritionists worked well in an effective interdisciplinary partnership when teaching medical students, providing a good model for further work in a healthcare setting.